Surfactant Therapy for Respiratory Distress Syndrome in High- and Ultra-High-Altitude Settings - Duan, Xudong; Li, Jiujun; Chen, Long; Shi, Yuan; Chen, Xianyang; Xue, Teng; Liu, Chongde; Wang, Xiaorong; Qiu, Quanfang; Yu, Zhen; Qiang, Bacuozhen; Wu, Hong; et al. (Frontiers in Pediatrics, 2022)
Objective: To investigate the therapeutic effect of surfactant replacement therapy (SRT) on respiratory distress syndrome (RDS) in premature infants in the Qinghai-Tibet Plateau. Material and Methods: This multi-center retrospective cohort study collected and screened reasonable clinical data of 337 premature infants with RDS from 10 hospitals in the Qinghai-Tibet Plateau from 2015 to 2017. We grouped the cases by rationally analyzing their baseline characteristics, using logistic analysis to evaluate each factor’s effect on the prognosis of the infants, and comparing the short-term improvement in blood gas and mortality after SRT treatment at different altitudes, in high-altitude (1500–3500 m) and ultra-high-altitude (3500–5500 m) groups. Results: Independent of altitude, the mortality rate of children with RDS in the SRT group was significantly lower than that of children in the non-SRT group (both P < 0.05). The effect of SRT on preterm infants with RDS in the high-altitude group (odds ratio [OR] = 0.44, 95% confidence interval [CI] = 0.22–0.87, P = 0.02) was better than that in the infants in the ultra-high-altitude group (OR = 0.26, 95% CI = 0.13–0.58, P < 0.01), with death rates of 34.34% and 49.71%, respectively. Similarly, after SRT, the improvement of PaO2/FiO2 and pH of children at high-altitude was significantly better than those of children at ultra-high-altitude (all P < 0.01). Conclusions: SRT plays a prominent role in curing infants with RDS in both high and ultra-high-altitude regions, although with better effects at high rather than ultra-high-altitude. This study provides a basis for further large-scale studies on SRT for RDS treatment at high altitudes.